The Comprehension of the Tablighi Jama'at in Pakauman Ulu Village About QS Ali-Imran [3]: 110 in the Khuruj Movement - Tsaaqib, Ahmad (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
The Khuruj movement as a result of the reception or understanding of the Tablighi Jama'ah group which has an influence related to da'wah in society is the starting point of this research. The understanding of the Tablighi Jama'ah which is based on QS Ali-Imran [3]: 110 becomes the material object of the study. This study uses a descriptive-qualitative method that describes data in the field as a primary source and is supplemented with secondary data from various previous research literature. The results of this study are that the Khuruj movement for the Tablighi Jama'ah is considered the key to their movement culturally touching all levels of society and is strategic. The results of the analysis as a conclusion from this study show that understanding of QS Ali-Imran [3]:110 tends to be textually related to the word ukhrijat which means going out of the house or place of residence to preach as the duty of the Prophets and Apostles to reach the best people. This understanding has implications, namely the existence of the Khuruj movement which is considered a benchmark of faith and religious understanding for the tabligh congregation. Then the researcher also relates the relevance of the Da'wah concept of the Tablighi Jama'ah and the challenges of da'wah in the era of society 5.0.